2021
DOI: 10.4103/ijo.ijo_3658_20
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal imaging of eyes with metamorphopsia after vitrectomy for rhegmatogenous retinal detachment

Abstract: Purpose: To assess the retinal features in eyes with postoperative metamorphopsia (POM) following rhegmatogenous retinal detachment (RRD) repair using multimodal imaging (MMI). Methods: In this cross-sectional; case-control study, patients after successful RRD repair following 25-gauge vitrectomy, clear vitreous cavity, and corrected distance visual acuity (CDVA)>20/200 were categorized using Amsler chart: cases with POM and controls without POM. MMI was performed on sw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Research has been conducted in order to identify factors associated with postoperative metamorphopsia following successful vitrectomy for retinal detachment. Using SS-OCT, Kumar and colleagues found that the preoperative extent of the detachment, postoperative foveal contour, and the continuity of the ellipsoid zone are significantly associated with the occurrence of postoperative metamorphopsia [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has been conducted in order to identify factors associated with postoperative metamorphopsia following successful vitrectomy for retinal detachment. Using SS-OCT, Kumar and colleagues found that the preoperative extent of the detachment, postoperative foveal contour, and the continuity of the ellipsoid zone are significantly associated with the occurrence of postoperative metamorphopsia [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among the potential biomarkers predicting functional recovery, the grade of detachment and the extent of cystoid macular edema seems promising in eyes with a detached fovea, as well as the integrity of the ellipsoid zone [ 14 , 30 ]. The extent of the detachment, the postoperative foveal contour, the integrity of the ellipsoid zone and of the external limiting membrane, and the presence of outer retinal folds, seem to be predictors of visual prognoses and metamorphopsia following a successful vitrectomy [ 12 , 15 , 16 , 17 , 22 , 28 , 48 , 49 ]. In addition, the thickness of the inner and outer segments of the photoreceptors, and thickness changes in the outer nuclear layer, may be predictors of the final visual outcome [ 19 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this table, we summarized the observations of MCI and its advantages found in published papers. The list is not exhaustive; however, it highlights the salient features of different retinal and choroidal disorders [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38].…”
Section: Discussionmentioning
confidence: 99%